If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -3(2x + -16) = -32 Reorder the terms: -4x + -3(-16 + 2x) = -32 -4x + (-16 * -3 + 2x * -3) = -32 -4x + (48 + -6x) = -32 Reorder the terms: 48 + -4x + -6x = -32 Combine like terms: -4x + -6x = -10x 48 + -10x = -32 Solving 48 + -10x = -32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + -10x = -32 + -48 Combine like terms: 48 + -48 = 0 0 + -10x = -32 + -48 -10x = -32 + -48 Combine like terms: -32 + -48 = -80 -10x = -80 Divide each side by '-10'. x = 8 Simplifying x = 8
| 4(3n+1)=52 | | 6b=4b+10 | | 1/4(8x-4)= | | -4n^2-6n+9=9 | | 5x+40=15x+100 | | 2(2n+5)=18 | | 9-6c=-5c | | 63^2/6 | | 294/420=511/w | | 5y-7-2y=0 | | -9+9y=10y | | 35/y=65/39 | | 9z=6+3z | | 12x-12=6x+32+2x | | 6/7×=9/14 | | 8x+17=49 | | 4x+5x-2x+x= | | 28-u=258 | | -4n-6n+9=9 | | 2y^3-32y^2-450y=0 | | 6/s=15/17.5 | | 6(6-3)-3= | | -14m-11=85 | | 2/3m-2=10 | | 2x=x-2+54 | | 975/195=p/1 | | (2y+8x)= | | -8(1+4x)-168= | | 48/96=g/6 | | 8+4=-4 | | 17-19=-2x | | (x-2)(x+3+3i)(x+3-3i)=0 |